2014
DOI: 10.1080/08916152.2014.883449
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cross Wind Conditions on Efficiency of Heller Dry Cooling Tower

Abstract: Performance of a Heller cooling tower under wind conditions has been investigated by measuring wind velocity and its direction around the tower and inlet and outlet water flow rates and temperatures. Results show that air suction at the tower prevents flow separation at its periphery. The tower front cooling sectors experience better airflow distribution compared to sectors parallel to wind direction, which improves their thermal performance by about 20% compared to still-air conditions. Airflow pattern around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…Cross ventilation is experienced and the hot air from the windward section penetrates into the leeward section. Similar trends are also reported in Ardekani's [84] full-scale measurements. Crosswind effect on the overall tower performance Table 2-5 lists the previous research result of the crosswind effect on the NDDCTV.…”
Section: Crosswind Effect On the Nddctvsupporting
confidence: 75%
See 1 more Smart Citation
“…Cross ventilation is experienced and the hot air from the windward section penetrates into the leeward section. Similar trends are also reported in Ardekani's [84] full-scale measurements. Crosswind effect on the overall tower performance Table 2-5 lists the previous research result of the crosswind effect on the NDDCTV.…”
Section: Crosswind Effect On the Nddctvsupporting
confidence: 75%
“…More detailed data was reported by Ardenikani [84] on a 92m NDDCTV. In his paper, heat exchangers of the cooling tower are divided into 6 sections.…”
Section: Aerodynamic Behaviours and Heat Exchanger Performancementioning
confidence: 99%
“…When evaluating the 3 effect of ambient temperature, heat rejection of the NDDCT is converted to the form 4 that is proportional to the power function of initial temperature difference of the tower, 5 using the theory of similar triangles. Heat rejection of the NDDCT under windy 6 condition is simply calculated based on the outlet air velocity obtained bya proposed 7 algorithm. Although thistheoretical model is inappropriate atcrosswind velocity higher 8 than the critical wind velocity, it's still meaningful for thermal performance prediction 9 of the NDDCT, because thiscritical wind velocityis usually large and uncommon in 10 the practical operation of the tower.Testing work for a 600MW th and other two 11 NDDCTs is conducted using this theoretical model flexibly, and the predictions agree 12 well with practical measurement data or results available in the existing literatures.…”
mentioning
confidence: 99%
“…12 To figure out performance variation caused by ambient condition, there are two 13 main kinds of methods, one is experimental research, and the other is numerical 14 research, sometimes verified by experiment under certain conditions. As for 15 experimental research,Ardekani et al [7] experimentally evaluated thermal 16 performance of the cooling tower under actual wind conditions prevailing around the 17 tower. These measurements showed that the tower front cooling sectors experience 18 better airflow distribution comparedto sectors parallel to wind direction, which 19 improves their thermal performance by about 20%compared to still-air conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation